Platinum-group elements (PGE) and their principal carriers in metal-rich black shales: an overview with a new data from Mo-Ni-PGE black shales (Zunyi region, Guizhou Province, south China) - Pasava,J.; Zaccarini,F.; Aiglsperger,T.; Vymazalova,A. (Journal of Geosciences, 2013)
Lower Cambrian Mo-Ni sulfidic black shales from the Huangjiawan mine (Guizhou Province, south China) have anomalous platinum-group elements (PGE) concentrations (up to ˜1 ppm in total). In order to identify principal PGE carriers, we used heavy mineral separates which were produced by innovative hydroseparation techniques. Subsequent detailed mineralogical study using electron microprobe did not result in the identification of discrete platinum-group minerals. Pyrite (grainy, not framboidal), millerite and gersdorffite that were identified in our heavy concentrate were analyzed for PGE and Re. We found that they contain the following concentrations of PGE and Re: pyrite (up to 490 ppm Pt, 390 ppm Pd and 220 ppm Rh), millerite (up to 530 ppm Pt, 430 ppm Pd and 190 ppm Rh) and gersdorffite (up to 410 ppm Pt and 320 ppm Pd; no Rh detected). Rhenium was detected only in grainy pyrite (up to 1060 ppm). It was found that despite anomalous PGE concentrations, the Mo-Ni black shales do not contain any platinum-group minerals and that the PGE are bound to pyrite and Ni-sulfides (millerite and gersdorffite).
Keywords: Mo-Ni-PGE black shale; PGE concentrations in pyrite and Ni-sulfides; Re concentration in pyrite; hydroseparation; electron microprobe study; south China